Red mud-biomass co-pyrolysis iron-carbon composite material, and preparation method and application thereof

CN122955461APending Publication Date: 2026-10-23CHONGQING CHEM IND VOCATIONAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611250389.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但因为其自身理化性质的限制使得生物碳对Cr(Ⅵ)的去除仍然有提升的空间

Benefits of technology

[0020]本发明采用赤泥和大薸共热解制备铁碳复合材料,对水中的Cr(Ⅵ)具有氧化还原作用,能将Cr(Ⅵ)还原为Cr(Ⅲ);Cr(Ⅲ)与Fe3+生成FeCr2O4共沉淀物以达到去除的目的。同时该复合材料含有含氧官能团能与Cr(Ⅵ)生成络合物以达到固定铁与铬的目的。本发明将大薸和赤泥进行共热解可以高效的去除六价铬,为利用大宗污染物赤泥提供了一种解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955461A_ABST
    Figure CN122955461A_ABST
Patent Text Reader

Abstract

The application discloses a kind of red mud biomass co-pyrolysis iron-carbon composite material and its preparation method and application, prepare according to the following steps: (1) wash with water after putting into oven and drying after grinding and sieving of Hygrophila difformis; (2) red mud is dried, ground and sieved; (3) after mixing red mud and Hygrophila difformis, put into porcelain boat with cover, in nitrogen atmosphere pyrolysis to obtain product.The application adopts red mud and Hygrophila difformis co-pyrolysis to prepare iron-carbon composite material, has oxidation-reduction effect on Cr (Ⅵ) in water, can reduce Cr (Ⅵ) to Cr (Ⅲ);Cr (Ⅲ) and Fe 3+ FeCr2O4 coprecipitate is generated to achieve the purpose of removal.Simultaneously, the composite material contains oxygen-containing functional groups that can form complexes with Cr (Ⅵ) to achieve the purpose of fixing iron and chromium. The co-pyrolysis of Hygrophila difformis and red mud in the application can efficiently remove hexavalent chromium, providing a solution for utilizing the bulk pollutant red mud.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of solid waste resource utilization and water treatment technology, specifically to a red mud biomass co-pyrolysis iron-carbon composite material, its preparation method, and its application. Background Technology

[0002] Chromium is a heavy metal element that is widely found in nature and industry and is harmful to human health. It usually exists in the form of Cr(VI) or Cr(III). Among these, Cr(VI) is classified as a Class I pollutant by the state due to its higher toxicity, better solubility, and stronger migration. The national emission standard for Class I pollutants is less than 0.5 mg / L. -1 Cr(VI) is recognized as a Group 1 carcinogen by international public health organizations, making the removal of Cr(VI) from water extremely important. Currently, the main methods for removing Cr(VI) include chemical reduction, adsorption, chemical precipitation, and membrane separation. Among these, adsorption-reduction methods are often used for the removal of heavy metals due to their high removal rate, simple operation, and low cost.

[0003] Red mud is a highly alkaline industrial solid waste generated during the alumina production process from bauxite ore. Its pH is typically 10-13, making it extremely corrosive. It exhibits different shades of red depending on its iron oxide content. Its main components are iron oxide, silicon dioxide, alumina, and calcium oxide. Currently, the primary method of treating red mud is by stockpiling, which not only wastes significant land resources but also causes environmental pollution. Therefore, it is essential to utilize red mud as a resource.

[0004] Water hyacinth, commonly known as water lettuce, water lily, or large-leaved lily, is a floating aquatic herbaceous plant belonging to the genus *Isodon* in the family Araceae. Native to Brazil in South America, it is now widely distributed in tropical and subtropical waters of my country. While a typical invasive alien species, it is also a commonly used aquatic remediation plant in the field of water environment restoration, possessing both ecological hazards and resource utilization value. It is widely used in research on wastewater treatment, heavy metal enrichment, and organic pollutant removal. Water hyacinth biomass has excellent nutrient transport and carbon sequestration capabilities, making it a preferred choice for the ecological restoration of various types of polluted water bodies due to its rapid growth rate. However, due to limitations in its physicochemical properties, there is still room for improvement in the removal of Cr(VI) by biochar. Summary of the Invention

[0005] To address the aforementioned technical problems, the present invention aims to provide a method for preparing a red mud biomass co-pyrolysis iron-carbon composite material. A second objective is to provide the red mud biomass co-pyrolysis iron-carbon composite material thus prepared, and a third objective is to provide its applications. This method can efficiently remove hexavalent chromium, providing a solution for utilizing red mud, a major pollutant.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a red mud biomass co-pyrolysis iron-carbon composite material, characterized by the following steps:

[0007] (1) Wash the water hyacinth with water, dry it in an oven, crush it and sieve it;

[0008] (2) The red mud is dried, crushed, and sieved;

[0009] (3) After mixing red mud and piss, put them into a covered porcelain boat, place them in a tube furnace, and pyrolyze them under a nitrogen atmosphere to obtain the product.

[0010] In the above scheme: drying is carried out at 80-90℃, and the dried red mud and large water chestnuts are both passed through a 70-80 mesh sieve.

[0011] In the above scheme, the pyrolysis temperature is 500-900℃.

[0012] In the above scheme, the pyrolysis temperature is 700℃.

[0013] In the above scheme, the mass ratio of red mud to water hyacinth is 2:1-1:4.

[0014] In the above scheme, the mass ratio of red mud to water hyacinth is 1:2 or 1:3.

[0015] In the above scheme, the pyrolysis time is 1-3 hours.

[0016] In the above scheme, the pyrolysis time is 2 hours.

[0017] A method for preparing a red mud biomass co-pyrolysis iron-carbon composite material obtained from vegetation.

[0018] Application of the aforementioned red mud biomass co-pyrolysis iron-carbon composite material in the reduction removal of Cr(VI) from water.

[0019] Beneficial effects:

[0020] This invention utilizes the co-pyrolysis of red mud and water hyacinth to prepare an iron-carbon composite material, which exhibits redox activity against Cr(VI) in water, reducing Cr(VI) to Cr(III); Cr(III) reacts with Fe 3+ FeCr₂O₄ coprecipitates are generated to achieve the removal purpose. Simultaneously, the composite material contains oxygen-containing functional groups that can form complexes with Cr(VI) to fix iron and chromium. This invention utilizes the co-pyrolysis of peat moss and red mud to efficiently remove hexavalent chromium, providing a solution for utilizing red mud, a major pollutant. Attached Figure Description

[0021] Figure 1FT-IR spectra of water hyacinth, red mud, Fe / C-CMs and Fe / C-CMs after reaction,

[0022] Figure 2 The XRD patterns are of pampas grass, red mud, Fe / C-CMs, and Fe / C-CMs after reaction.

[0023] Figure 3 The image shows the TG-DTA diagrams of pampas grass, red mud, Fe / C-CMs, and Fe / C-CMs after their reaction.

[0024] Figure 4 Figure showing the effect of different Fe / C-CMs sintering temperatures on Cr(VI) removal rate

[0025] Figure 5 The graph shows the effect of different red mud / piper mass ratios on Cr(VI) removal rate.

[0026] Figure 6 The graph shows the effect of different Fe / C-CMs sintering (c) on the Cr(VI) removal rate.

[0027] Figure 7 The graph shows the effect of different initial solution concentrations on the Cr(VI) removal rate.

[0028] Figure 8 The graph shows the effect of the initial pH of the Cr(VI) standard solution on the Cr(VI) removal rate.

[0029] Figure 9 The graph shows the effect of Fe / C-CMs dosage (c) on Cr(VI) removal rate.

[0030] Figure 10 To process the XPS spectra of Fe / C-CMs before and after Cr(VI),

[0031] Figure 11 To process the XPS spectra of Fe / C-CMs before and after Cr(VI) and the corresponding Cr 2p,

[0032] Figure 12 This is a narrow spectrum of Fe 2p before the reaction.

[0033] Figure 13 This is a narrow spectrum of Fe 2p after the reaction.

[0034] Figure 14 SEM images of Fe / C-CMs before and after Cr(VI) processing.

[0035] Figure 15 Figures showing the speciation of chromium in the solution before and after Fe / C-CMs treatment. Detailed Implementation

[0036] The present invention will now be further described with reference to the accompanying drawings and embodiments.

[0037] Example 1

[0038] Preparation of composite materials

[0039] After washing the water spinach with water, dry it in an 80 ℃ oven for 24 h, then crush it and pass it through a 70-80 mesh sieve. Dry the red mud, crush it, and also pass it through a 200 μm sieve. Mix the red mud and water spinach in different ratios (2:1, 1:1, 1:2, 1:3, 1:4) and place them in a covered ceramic boat. Pyrolysis is then performed in an OTF-1200X high-temperature tube furnace under nitrogen atmosphere. The pyrolysis temperatures were set to 500 ℃, 600 ℃, 700 ℃, 800 ℃, and 900 ℃, respectively; the pyrolysis times were set to 1 h, 1.5 h, 2 h, 2.5 h, and 3 h, respectively. After cooling to room temperature, the mixture is ready for use.

[0040] Adsorption experiment

[0041] Accurately weigh 0.2835 g of potassium dichromate powder and dissolve it in 1000 mL of deionized water to prepare a 100 mg / L Cr(VI) stock solution. This solution was then diluted to different concentrations before use. Different masses of Fe / C-CMs were added under different pH conditions, and the mixture was stirred. Samples were taken at 1, 3, 5, 10, 15, 20, and 30 min, filtered, and the absorbance was measured at 540 nm using diphenylcarbazide spectrophotometry to analyze the Cr(VI) content in the solution.

[0042] 1. Selection of sintering temperature

[0043] The effect of pyrolysis temperature on Cr(VI) removal was investigated at a red mud to pampas grass mass ratio of 1:2 and a pyrolysis time of 2 h. Adsorption experiments were conducted at an initial Cr(VI) concentration of 25 mg / L, an optimal pH of 2, and an optimal dosage of 0.3 g / L. Figure 4It can be seen that the removal efficiency significantly increases to 98% when the temperature reaches 700 °C. However, the efficiency decreases noticeably when the temperature rises to 800 °C, but becomes very effective again at 98% when the temperature exceeds 900 °C. This is likely because the *Isatis indicus* releases volatile reducing gases during high-temperature pyrolysis, reducing the iron oxide in the red mud to zero-valent iron, thereby reducing Cr(VI) in the water. Thermogravimetric analysis shows that at 800 °C, further decomposition of certain substances in the *Isatis indicus* prevents the reduction of iron oxide in the red mud to zero-valent iron. At 900 °C, the red mud itself may be able to be reduced to zero-valent iron through high-temperature reduction, thus achieving the reduction and removal effect of Cr(VI). Considering all factors, 700 °C was chosen as the pyrolysis temperature for Fe / C-CMs.

[0044] 2. Selection of Red Mud / Phyllanthus Mass Ratio

[0045] The optimal mass ratio of red mud to water hyacinth was investigated under the conditions of pyrolysis temperature of 700 °C and pyrolysis time of 2 h. Adsorption experiments were conducted at an initial Cr(VI) concentration of 25 mg / L, an optimal pH of 2, and an optimal dosage of 0.3 g / L. Figure 5 The results showed that the Fe / C-CMs obtained by pyrolysis after mixing exhibited a significantly higher Cr(VI) removal efficiency than either red mud or water hyacinth alone, with ratios of 1:2 and 1:3 showing the best results. After 30 minutes of reaction, the Cr(VI) removal rate reached over 98%. This indicates that increasing the proportion of water hyacinth increases the amount of volatile reducing gases, allowing for the complete reduction of iron oxide in the Fe / C-CMs to zero-valent iron, thus increasing the Cr(VI) removal rate. However, a decrease in the proportion of red mud leads to a reduction in the amount of reducible iron oxide, thereby affecting the Cr(VI) removal efficiency. Considering that red mud is a large-scale waste product, a 1:2 ratio was chosen for further research.

[0046] 3 Effect of pyrolysis time

[0047] The pyrolysis time was investigated at a red mud to water hyacinth mass ratio of 1:2 and a pyrolysis temperature of 700 °C. Adsorption experiments were conducted at an initial Cr(VI) concentration of 25 mg / L, an optimal pH of 2, and an optimal dosage of 0.3 g / L. Figure 6The results show that the removal rate of Cr(VI) by Fe / C-CMs increases slightly as the pyrolysis time increases from 1 h to 2 h. When the pyrolysis time reaches 3 h, the removal efficiency of Cr(VI) by Fe / C-CMs begins to decline sharply. This may be because the sintering time is too long, leading to the collapse or fusion of the pore structure, reducing the activity of functional groups and thus decreasing the removal efficiency of Cr(VI). Based on these results, 2 h was selected as the pyrolysis time for Fe / C-CMs.

[0048] 4. Structural characterization

[0049] 4.1 FT-IR analysis

[0050] Figure 1 The images show the FT-IR spectra of *Isatis tinctoria*, red mud, and Fe / C-CMs. The figures reveal significant differences in the functional groups of the three materials. Unmodified red mud has a peak density of 579 cm⁻¹. -1 There was a very obvious Fe-O stretching vibration peak at the point, but after modification with biochar, the characteristic peak disappeared, suggesting that Fe2O3 may have been generated. 0 The vibrations of its metallic bonds show almost no absorption in the infrared region. Furthermore, the modified Fe / C-CMs possess functional groups with reductive adsorption properties, such as -OH, -C=O, -C=C, and -CO, which are beneficial for removing Cr(VI). After Fe / C-CMs treated Cr(VI), the peak intensities of both the -CO and Fe-O bonds decreased, indicating that these functional groups underwent coordination complexation with Cr(VI) and participated in Cr(VI) removal. Simultaneously, the significant shift and weakening of the O-Si-O bond peak intensity suggests that a "π-π" interaction may have occurred between Cr(VI) and the O-Si-O bond. Therefore, based on this structure, it can be inferred that the mechanism of Cr(VI) adsorption in water using red mud-modified biochar mainly relies on hydroxyl and carbonyl groups supporting zero-valent iron (Fe0), and the "π-π" interaction between Cr(VI) and the O-Si-O bond.

[0051] 4.2 XRD Analysis

[0052] Figure 2 The XRD patterns of the three materials show that the red mud contains a large amount of Fe2O3, Fe3O4, Al(OH)3, TiO2, and other substances after pyrolysis. In the case of *Isodon stenoptera*, amorphous carbon peaks appear at 2θ=24° and 2θ=42°, corresponding to the (002) and (100) crystal planes of amorphous carbon, respectively. This structure can increase the electron transfer rate between zero-valent iron and Cr(VI), thereby promoting the reduction of Cr(VI). After mixed pyrolysis modification, the diffraction peaks of the metal oxides are significantly reduced, replaced by a distinct Fe peak at around 2θ=45°. 0The characteristic diffraction peaks indicate that a large amount of Fe2O3 and Fe3O4 in the red mud were converted into Fe after being modified with biochar. 0 This is consistent with the results of infrared spectroscopy analysis, proving the modification was successful. After Cr(VI) adsorption experiments, Fe / C-CMs showed zero-valent iron (Fe)... 0) The significant decrease followed by the appearance of FeCr2O4 indicates the possible presence of trivalent iron (Fe). 3+ ) coprecipitates with Cr(III) through a redox reaction, reducing Cr(VI) to Cr(III), while zero-valent iron (Fe) undergoes a redox reaction. 0 It is oxidized to ferrous iron (Fe2+). 2+ ) and trivalent iron (Fe) 3+ Studies have mentioned that iron-chromium complexes facilitate the further fixation of iron and chromium. Therefore, the reaction mechanism for treating Cr(VI) in water using Fe / C-CMs involves a redox reaction, reducing Cr(VI) to Cr(III), which then reacts with Cr(III) oxidized to ferric iron (Fe). 3+ Zero-valent iron (Fe) 0 Coprecipitates are formed.

[0053] 4.3 Thermogravimetric Analysis

[0054] Figure 3 The TG curve can be divided into four parts. In the initial stage (35℃~120℃), the weight loss rates of both *Ipomoea aquatica* and *Ipomoea aquatica-red mud* are relatively low, which is caused by the evaporation of free water in the biomass. Around 120℃~330℃, cellulose and hemicellulose in the biomass begin to pyrolyze. In the stage from 330℃ to 700℃, the weight loss rate of both is rapid and the difference in weight loss rate is significant. This may be because the pyrolysis products of *Ipomoea aquatica* in *Ipomoea aquatica-red mud* may have reacted with the red mud, weakening the degree of pyrolysis. When the temperature reaches 700℃, the weight of both tends to stabilize, and the difference in weight loss rate is not significant. However, after reaching 800℃, the weight begins to decrease again, possibly because the high temperature causes the gasification of certain substances in the biochar. In *Ipomoea aquatica-red mud*, the pyrolysis rate is slower due to the influence of the red mud. Furthermore, the graph shows that the mass of red mud begins to decrease after pyrolysis, then stabilizes after 400 °C, with a stable mass change rate of around 87%, significantly higher than that of biomass and mixed Fe / C-CMs. This indicates that the main substances remaining after high-temperature pyrolysis are elements from the red mud. Biomass, on the other hand, provides reducing gases that facilitate the reduction of iron oxide in the red mud to zero-valent iron.

[0055] 5. Adsorption of Cr(VI)

[0056] 5.1 Effect of initial Cr(VI) concentration

[0057] Figure 7It can be seen that when the initial concentration is ≤ 25 mg / L, the removal rate of Cr(VI) by Fe / C-CMs remains at a very high level. When the concentration is too high, the removal rate drops significantly. When the concentration reaches 50 mg / L, the removal rate is only 58%. This is because when the amount of Fe / C-CMs added is fixed, the number of active sites that can react with Cr(VI) is also fixed. When the concentration is low, Fe / C-CMs have enough active sites to react with Cr(VI). As the concentration of Cr(VI) increases, the number of Cr(VI) competing for active sites also increases, resulting in insufficient active sites on the surface of Fe / C-CMs. The remaining Cr(VI) cannot be adsorbed onto the surface of Fe / C-CMs for reaction, thus resulting in poor removal effect.

[0058] 5.2 Effect of initial pH

[0059] Figure 8 The figure shows the removal efficiency of Fe / C-CMs for Cr(VI) at different pH values. As can be seen from the figure, the removal efficiency decreases with increasing pH. When pH ≤ 2, the removal rate of Cr(VI) reaches 98%, but when the pH rises to 3, the removal rate drops to only 53%. This indicates that the removal efficiency of Cr(VI) is much greater in acidic environments than in alkaline environments. This is because Cr(VI) in aqueous solutions usually exists as an anion with a large negative charge. Therefore, when a large amount of H+ is present in the aqueous solution... + When the solution is alkaline, the positive charge on the Fe / C-CMs surface increases, making it easier to attract Cr(VI) anions to the Fe / C-CMs surface via electrostatic adsorption and react. When the solution is alkaline, a large number of OH- ions will be present on the material surface. - Due to the mutual repulsion principle, it is difficult to attract Cr(VI) anions to the material surface for reaction, thus greatly reducing the degradation rate. Furthermore, research indicates that the main active substance for removing Cr(VI) is Fe. 0 Fe produced after corrosion 2+ An acidic environment can accelerate this corrosion process, thereby accelerating the removal of Cr(VI).

[0060] 5.3 Impact of Dosage

[0061] Figure 9 This study investigated the effect of Fe / C-CMs on the removal of Cr(VI) from aqueous solution under different dosages. It can be seen that the removal efficiency of Cr(VI) increases with increasing dosage, reaching over 98% at a dosage of 0.3 g / L. This is mainly attributed to the increased number of available active sites and the reduction of reducing components (such as Fe) in the red mud. 2+The total amount increases. When the dosage reaches the critical value, the system enters the optimal treatment range. At this time, the active sites and pollutant concentrations reach an ideal ratio, and the synergistic effect of surface adsorption and chemical reduction is most significant. In this stage, the abundant oxygen-containing functional groups (carboxyl groups, hydroxyl groups, etc.) on the surface of biochar and the iron oxides loaded on red mud form a dual-action network, which captures Cr(VI) anions through electrostatic attraction and reduces them to low-toxicity Cr(III) through electron transfer.

[0062] 6. Mechanism Analysis

[0063] 6.1 XPS Analysis

[0064] Figure 10 The image shows the XPS spectra of Fe / C-CMs before and after treating Cr(VI) simulated wastewater. Analysis of the overall XPS spectrum reveals characteristic peaks for Cr in the treated Fe / C-CMs, indicating that Cr(VI) or Cr(VI) reactants were adsorbed onto the Fe / C-CMs.

[0065] Analysis of the narrow spectrum of Cr2p after the reaction Figure 11 It can be found that most of the Cr elements fixed on Fe / C-CMs are Cr(Ⅲ) at 577.8 eV, and a small amount of Cr(Ⅵ) at 579.3 eV. This indicates that a large amount of Cr(Ⅵ) in the solution is adsorbed to the surface of Fe / C-CMs and reduced to Cr(Ⅲ), and fixed on Fe / C-CMs in the form of Cr(OH)3 through complexation adsorption.

[0066] Narrow spectrum of Fe2p before and after the reaction ( Figure 12 , 13 Analysis revealed characteristic peaks for FeO, Fe₂O₃, and Fe(III) at 710.10 eV, 712.01 eV, and 714.33 eV, respectively. However, due to the potential presence of organic matter encapsulating the surface, Fe was not easily detected directly. 0 After treating the simulated Cr(VI) wastewater, the mass fraction of FeO on the material surface decreased from 64.87% to 54.07%, while the mass fractions of Fe2O3 and Fe(III) increased from 17.56% and 17.56% to 20.23% and 25.7%, respectively. This further demonstrates that a redox reaction occurred in the solution. In summary, the surface of Fe / C-CMs adsorbed both reduced Cr(III) and unreduced Cr(VI), further demonstrating the combined effect of adsorption and reduction during the removal of hexavalent chromium by Fe / C-CMs.

[0067] 6.2 SEM comparison before and after the reaction

[0068] SEM images of Fe / C-CMs before and after the reaction are shown below. Figure 14 As shown, (a) is the SEM image before the reaction, where the material structure is loose and exhibits an irregular shape. EDS results show that the iron element is evenly distributed on the surface of this structure, indicating successful iron loading. As shown in (b), after reacting with Cr(VI), the material surface is smooth, the structure is elliptical, and the pores are smaller due to the adsorption of Cr(VI). EDS analysis results show that the chromium element is significantly more abundant than before the reaction, confirming that Fe / C-CMs have an adsorption effect on the removal of Cr(VI), which is consistent with the total spectrum analysis of XPS.

[0069] 6.3 Analysis of Chromium Speciation in Solutions Before and After Treatment

[0070] Depend on Figure 15 As the reaction time increases, Cr(VI) gradually decreases while Cr(III) gradually increases. This indicates that a reduction reaction occurred in the solution. Combined with XRD analysis, this likely suggests that the iron and iron oxides in the Fe / C-CMs react with Cr(VI) in the solution, reducing Cr(VI) to Cr(III). The zero-valent iron (Fe₂O₃) supported on the biochar Fe / C-CMs is then oxidized to the highly oxidizing divalent iron (Fe₂O₃) under acidic conditions. 2+ ) and trivalent iron (Fe 3+ ).

[0071] Based on the above analysis, it is speculated that the mechanism by which Fe / C-CMs remove hexavalent chromium is that Cr(VI) in aqueous solution typically exists in the form of Cr₂O₇. 2- HCrO4 - HCrO4 - Under acidic conditions, it undergoes a redox reaction with zero-valent iron in Fe / C-CMs, Fe 0 Oxidized to Fe 2+ It is further oxidized to ferric iron, and Cr(VI) is reduced to Cr(III), thereby achieving the removal of Cr(VI) from the aqueous solution.

[0072] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a red mud biomass co-pyrolysis iron-carbon composite material, characterized in that, Prepare according to the following steps: (1) Wash the water hyacinth with water, dry it in an oven, crush it and sieve it; (2) The red mud is dried, crushed, and sieved; (3) After mixing red mud and piss, put them into a covered porcelain boat, place them in a tube furnace, and pyrolyze them under a nitrogen atmosphere to obtain the product.

2. The method for preparing the red mud biomass co-pyrolysis iron-carbon composite material according to claim 1, characterized in that: Drying is carried out at 80-90℃, and the dried red mud and large water chestnuts are passed through a 70-80 mesh sieve.

3. The method for preparing the red mud biomass co-pyrolysis iron-carbon composite material according to claim 1 or 2, characterized in that: The pyrolysis temperature is 500-900℃.

4. The method for preparing the red mud biomass co-pyrolysis iron-carbon composite material according to claim 3, characterized in that: The pyrolysis temperature is 700℃.

5. The method for preparing the red mud biomass co-pyrolysis iron-carbon composite material according to claim 4, characterized in that: The mass ratio of red mud to large water chestnut is 2:1-1:

4.

6. The method for preparing the red mud biomass co-pyrolysis iron-carbon composite material according to claim 5, characterized in that: The mass ratio of red mud to water hyacinth is 1:2 or 1:

3.

7. The method for preparing the red mud biomass co-pyrolysis iron-carbon composite material according to claim 4, characterized in that: The pyrolysis time is 1-3 hours.

8. The method for preparing the red mud biomass co-pyrolysis iron-carbon composite material according to claim 4, characterized in that: The pyrolysis time is 2 hours.

9. A method for preparing a red mud biomass co-pyrolysis iron-carbon composite material according to any one of claims 1-8, the red mud biomass co-pyrolysis iron-carbon composite material obtained from vegetation.

10. The application of the red mud biomass co-pyrolysis iron-carbon composite material as described in claim 9 in the reduction removal of Cr(VI) from water.